Biological investigations - Dolphin, Warren D. (McGraw-Hill Higher Education, 2007)
This lab manual is for a one or two-semester majors level general biology lab and can be used with any majors-level general biology textbook. The labs are investigative and ask students to use more critical thinking and hands-on learning. The author emphasizes investigative, quantitative, and comparative approaches to studying the life sciences.